2000
DOI: 10.1023/a:1009406315729
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Cyst aspiration and conservative management showed similar implantation and pregnancy rates, in patients who develop functional ovarian cysts after pituitary down-regulation following luteal phase gonadotropin-releasing hormone agonist administration. Prospective studies are needed to confirm this trend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…In this study, the formation rate of functional ovarian cysts was 10.1% (341/3375) in patients treated with follicular-phase depot GnRH agonist, similar to the 9.3% after the luteal-phase suppression as reported by Qublan et al (23). Other investigators found that agonist injection in the follicular phase was associated with a higher rate of cyst formation (14,26). However, their The multiple regression model included variables that showed significant differences on univariate analysis at P < 0.1. findings contradict a previous study in which the event incidence was higher when administered at mid-luteal phase than menstruation (15.4% vs. 13.6%) (27).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In this study, the formation rate of functional ovarian cysts was 10.1% (341/3375) in patients treated with follicular-phase depot GnRH agonist, similar to the 9.3% after the luteal-phase suppression as reported by Qublan et al (23). Other investigators found that agonist injection in the follicular phase was associated with a higher rate of cyst formation (14,26). However, their The multiple regression model included variables that showed significant differences on univariate analysis at P < 0.1. findings contradict a previous study in which the event incidence was higher when administered at mid-luteal phase than menstruation (15.4% vs. 13.6%) (27).…”
Section: Discussionsupporting
confidence: 87%
“…The effect of the ovarian cyst presence on pregnancy outcomes has been discussed frequently in COS treatment and fresh ET cycles, but the findings are conflicting. Some investigations point out that the existence of ovarian cysts increased the cycle cancellation rate, lowered oocyte number and quality, and compromised the pregnancy results (14,16,23,36). In such cases, the cysts inside the ovary would impede the final stages of the pre-ovulatory follicles, reduce the space for other follicles to develop, and damage the blood supply to the growing follicles (14,36), all contributing to poor oocyte results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As GnRH receptors have been described in the ovary and the presence of specific GnRH agonistic and antagonistic binding has been demonstrated in human luteinized granulosa cells, these compounds, particularly GnRH agonists, can induce the formation of functional follicular cysts (Mehta and Anand Kumar, 2000), probably as a result of their flare-up effects. The incidence of functional cysts has been reported to be in the range 2-40%, the frequency being higher in older women, when the administration of the agonist begins in the follicular phase rather than in mid-luteal phase, and in women with increased concentrations of basal FSH (Fiszbajn et al, 2000). Other disadvantages of GnRH agonists include hypo-oestrogenaemia and the requirement for a prolonged period of down-regulation, with subsequent high costs.…”
Section: Conventional Protocols For Ovarian Stimulation and The Role mentioning
confidence: 99%